Health Risk Assessment of Microplastic Contamination in Kamoning River Sampang, Madura - Astri Rino Okvitasari; Agus Muji Santoso; Retno Syahriawati Dewi; Muhammad Arus Samudro; Aurista Miftahatul Ilmah; Afifah Bilqis Faudya (Journal of Applied Sciences, Management and Engineering Technology, 2026)
Microplastics have become pervasive contaminants in riverine and coastal environments, raising concern about their implications for ecosystems and communities that rely on these waters. This study investigates microplastic contamination and associated risks in the Kamoning River, Sampang District, Madura, Indonesia, where residential, agricultural and port activities may drive substantial inputs of plastic debris. Surface water samples were collected at six stations representing upstream, midstream, urban, port and estuarine reaches, and analysed for microplastic abundance and morphology using sieving, chemical digestion and microscopic identification. Microplastic particles were quantified as fragments, fibres and films, and total abundances were expressed as particles per litre. To characterize potential risks, a screening-level risk quotient (RQ) approach was applied by comparing estimated exposure concentrations with literature-based reference values for ecological and human health endpoints. The average of microplastic abundances were in the order of 10⁴ particles per litre and increased from upstream to estuarine stations, with fragments as the dominant form at all locations. Calculated RQ values for short-term exposure via water use and local fish consumption ranged from 0.23 to 0.51, indicating low to moderate concern under current conditions. These findings show that the Kamoning River functions as a critical conduit and accumulation zone for microplastics, while present risk levels remain below commonly used thresholds. The study contributes a locally grounded, reproducible framework for linking microplastic abundance data to risk indicators that can support targeted plastic waste management and inform future monitoring and research in Indonesian river systems.